2016
DOI: 10.1128/genomea.00313-16
|View full text |Cite
|
Sign up to set email alerts
|

Correction for Johnson et al., Complete Genome Sequences for 59 Burkholderia Isolates, Both Pathogenic and Near Neighbor

Abstract: e00159-15, 2015.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
2
12
0
Order By: Relevance
“…For this confirmation, it was considered that they are unique continuous DNA regions absent in the available genome sequences of the published epidemic clones and longer than 10 kbp, flanked, at both sides, by homologous regions (especially those inserted immediately downstream of tRNA), and have lower (or higher) GC content compared with the rest of the genome ( Guo et al, 2017 ; Nunvar et al, 2017 ). The absence of DNA regions homologous to these unique GIs in the genomes of epidemic clones – B. cenocepacia ET12 and ST32 ( Holden et al, 2009 ; Nunvar et al, 2017 ) and B. multivorans ATCC_17616 and ATCC_BAA-247 ( Komatsu et al, 2003 ; Johnson et al, 2015 ; Johnson et al, 2016 ) – was confirmed and visualized by Progressive MAUVE whole genome pairwise alignment and ACT/Artemis ( Carver et al, 2005 ; Darling et al, 2010 ). Large DNA regions that respected those criteria but were not predicted by IslandViewer, were also manually identified and considered genuine-unique GIs.…”
Section: Methodsmentioning
confidence: 88%
“…For this confirmation, it was considered that they are unique continuous DNA regions absent in the available genome sequences of the published epidemic clones and longer than 10 kbp, flanked, at both sides, by homologous regions (especially those inserted immediately downstream of tRNA), and have lower (or higher) GC content compared with the rest of the genome ( Guo et al, 2017 ; Nunvar et al, 2017 ). The absence of DNA regions homologous to these unique GIs in the genomes of epidemic clones – B. cenocepacia ET12 and ST32 ( Holden et al, 2009 ; Nunvar et al, 2017 ) and B. multivorans ATCC_17616 and ATCC_BAA-247 ( Komatsu et al, 2003 ; Johnson et al, 2015 ; Johnson et al, 2016 ) – was confirmed and visualized by Progressive MAUVE whole genome pairwise alignment and ACT/Artemis ( Carver et al, 2005 ; Darling et al, 2010 ). Large DNA regions that respected those criteria but were not predicted by IslandViewer, were also manually identified and considered genuine-unique GIs.…”
Section: Methodsmentioning
confidence: 88%
“…nov. are present in GenBank and consist of strains MSMB121 and MSMB43 T (which is the same type strain used in this study but is listed with an alternative BioProject strain identifier, 2002721687 [BioProject no. PRJNA239255 ]) ( 34 , 35 ) with GenBank assembly accession numbers GCA_000385525 and GCA_000959325 , respectively. A comparative genomics approach using LS-BSR ( 25 ) was also performed with the B. pseudomallei genome strain K96243 ( BPSS1165 to BPSS1184 ).…”
Section: Methodsmentioning
confidence: 99%
“…nov. strains MSMB121 and MSMB122 are KF378608 and KF378609 , respectively. The complete whole-genome sequence of the strain MSMB121 was published under GenBank accession numbers CP004095 and CP004096 ( 34 , 35 ). The assembly for MSMB43 T was published under GenBank assembly number GCA_001513745 and that for MSMB122 under SRA numbers SRR1956040 and LNPD00000000 .…”
Section: Methodsmentioning
confidence: 99%
“…The de novo assembly was made with MIRA v4.0-1 ( 9 ) and CAP3 ( 10 ), which generated 23 contigs and a draft genome of 8.4 Mb. The N 50 value obtained was 574,923 bp, the genome was 95.06% of the B. gladioli ATCC 10248 reference genome size ( 11 ), and the G+C content estimated for the draft genome sequence was 68.04%. Prokka 1.12 ( 12 ) and the Rapid Annotations using Subsystem Technology (RAST) Web server ( 13 ) identified the presence of 7,155 coding sequence (CDS) regions and 7,540 genes, 76 of them for tRNA and 1 for transfer-messenger RNA (tmRNA).…”
Section: Genome Announcementmentioning
confidence: 93%